2021
DOI: 10.1016/j.annonc.2021.08.1494
|View full text |Cite
|
Sign up to set email alerts
|

1385P Phase II study of neoadjuvant camrelizumab combined with chemoradiation for locally advanced proximal gastric cancer (Neo-PLANET, NCT03631615)

Abstract: Most common D + T + CAPOX regimen related TEAEs were G1/2: anemia, thrombocytopenia, fatigue, diarrhea, nausea each in 3 pts. No related G3/4 toxicities; overall four G5 events; 1 related event pulmonary embolism. mITT analysis included 22 pts. Preliminary ORR in response evaluable (RE) mITT was 68% (13 PR, 6 SD, 1 NE, 2 pending first scan) and DCR 100%. In RE DKK1 high pts (n¼7) there was an ORR of 100% (6 PR, 1 NE) compared with DKK1 low pts (n¼9) ORR of 56% (5 PR, 4 SD). Median DoR and PFS were not reached.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Research on adjuvant chemotherapy for GC is ongoing and is expected to further improve the survival rates of patients with GC [ 37 38 39 40 ]. Although these findings support the importance of adjuvant chemotherapy, there is no consensus regarding the duration of adjuvant chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Research on adjuvant chemotherapy for GC is ongoing and is expected to further improve the survival rates of patients with GC [ 37 38 39 40 ]. Although these findings support the importance of adjuvant chemotherapy, there is no consensus regarding the duration of adjuvant chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…The original search identified a total of 602 publications, and the study retrieval process is depicted in Figure 1. Twenty studies met the inclusion criteria, including a total number of 753 patients, were included in this meta-analysis (17,(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38). Of these, 15 studies reported that patients received neoadjuvant immunotherapy combined with chemotherapy, which our meta-analysis mainly focused on.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have illustrated that the addition of radiotherapy ( 28 , 30 ) or anti-VEGF drugs ( 20 , 29 ) improved the effectiveness of neoadjuvant therapy. Our study reported that, compared with the addition of radiotherapy or anti-VEGF drugs with single neoadjuvant immunochemotherapy, the combination with radiotherapy did improve MPR rate but had a higher incidence of TRAEs.…”
Section: Discussionmentioning
confidence: 99%
“…Patients were required to receive four cycles of XELOX adjuvant chemotherapy within 4–6 weeks postoperatively. Results indicated that camrelizumab combined with radiation and chemotherapy was an effective treatment for patients with locally advanced GC, ORR was 93.3%, the pathological complete response (pCR) rate was 33.3%, the primary endpoint of the phase I trial, and the phase II trial was ongoing ( 70 , 71 ). Neoadjuvant concurrent chemoradiotherapy followed by surgery in patients with locally advanced esophageal, or GEJA, who received durvalumab showed an excellent survival benefit with 2-year recurrence-free survival and OS of 55.5% and 67.4%, respectively ( 72 ).…”
Section: Icis Combined With Other Treatments Of Advanced Gcmentioning
confidence: 99%